Toward automated non-destructive diagnosis of chloride attack on concrete structures by near infrared spectroscopy. (25th October 2021) - Watanabe, A.; Tokuda, S.; Mizuta, Y.; Miyamoto, S.; Nakanishi, T.; Furukawa, H.; Minagawa, H.
Graphical abstract: Highlights: Quantitative analysis by direct extraction of NIR absorption peak intensity. Selectivity problem due to overlaps of hydroxide peaks in characteristic absorption. NIR spectrum of synthesized Kuzel's salt, similar to Friedel's salt and monosulphate. Quantitative analysis based on Bayesian statistics for automatic peak identification. Correlation between extracted NIR peaks of Friedel's salt and XRD/XRF measurements. Abstract: This is a fundamental study of a non-destructive and contactless equipment to evaluate the chloride ion on concrete, with near infrared spectroscopy. Non-destructive measurements on Friedel's salt, generated by ingress of chloride ion into concrete, have been studied; characteristic absorption unique to each substance was utilized to qualitative and quantitative analyses. However, there has been a difficulty in separating absorption peak of Friedel' salt from that of other hydrates. This study investigates the method to extract the absorption peak of Friedel's salt by Bayes' theorem for quantitative evaluation, and its validity was confirmed using some conventional methods.